Tinjauan Hukum Tentang Hibah Dan Batasan Pemberian Hibah - Aris Priyadi (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2023)
A grant is a gift from one person to another where the giver is still alive. Materially, the existence of a grant hassomething to do with inheritance. Provisions/rules regarding grants in Indonesia are still pluralistic. Basically, anowner of property has the right and freedom to give/grant to anyone, including his children, provided that the gift(grant) does not cover and does not reduce other rights as heirs. If the conditions and pillars are met then the grantis valid. Giving grants according to Islamic law (Compilation of Islamic Law) is limited to a maximum of 1/3 (onethird) of the total assets of the grantor. In the event that grants are made to their children (heirs), then thelimitation is that grants must be made with the principle of justice. This grant limit is given to protect the rights ofthe heirs after the grantor dies. In addition to the maximum limits regulated in the Compilation of Islamic Law (KHI),customary law and the Civil Code also provide the same limits on grant grants. This is intended to protect theabsolute rights of the heirs and to avoid losses suffered by the heirs whose share cannot be reduced according to law(legitieme portie).